Effects of Transcranial Direct Current Stimulation (tDCS) on Pain Distress Tolerance: A Preliminary Study. Issue 8 (25th June 2015) - Mariano, Timothy Y.; van't Wout, Mascha; Jacobson, Benjamin L.; Garnaat, Sarah L.; Kirschner, Jason L.; Rasmussen, Steven A.; Greenberg, Benjamin D.
Abstract: Objective: Pain remains a critical medical challenge. Current treatments target nociception without addressing affective symptoms. Medically intractable pain is sometimes treated with cingulotomy or deep brain stimulation to increase tolerance of pain‐related distress. Transcranial direct current stimulation (tDCS) may noninvasively modulate cortical areas related to sensation and pain representations. The present study aimed to test the hypothesis that cathodal ("inhibitory") stimulation targeting left dorsal anterior cingulate cortex (dACC) would increase tolerance to distress from acute painful stimuli vs anodal stimulation. Methods: Forty healthy volunteers received both anodal and cathodal stimulation. During stimulation, we measured pain distress tolerance with three tasks: pressure algometer, cold pressor, and breath holding. We measured pain intensity with a visual‐analog scale before and after each task. Results: Mixed ANOVA revealed that mean cold pressor tolerance tended to be higher with cathodal vs anodal stimulation ( P  = 0.055) for participants self‐completing the task. Pressure algometer ( P  = 0.81) and breath holding tolerance ( P  = 0.19) did not significantly differ. The pressure algometer exhibited a statistically significant order effect irrespective of stimulation polarity (all P  < 0.008). Pain intensity ratings increased acutely after cold pressor and pressure algometer tasks (both P  < 0.01), but not after breath holding ( P  = 0.099). Cold pressor pain ratings tended to rise less after cathodal vs anodal tDCS ( P  = 0.072). Conclusions: Although our primary results were nonsignificant, there is a preliminary suggestion that cathodal tDCS targeting left dACC may increase pain distress tolerance to cold pressor. Pressure algometer results are consistent with task‐related sensitization. Future studies are needed to refine this novel approach for pain neuromodulation.